Internalisasi Profesionalisme Guru Melalui Program Asistensi Mengajar: Evaluasi Kesiapan Etika Dan Kinerja Mahasiswa Calon Pendidik - Munawir Munawir; Putri Naura Zahara; Siti Nur Azizah (LPPM Institut Pendidikan Nusantara Global, 2026)
This research aims to analyze the internalization of teacher professionalism among prospective teachers through the teaching assistance program. Teacher professionalism is a key factor in improving educational quality, requiring early preparation during higher education. This research employs a qualitative descriptive approach using a literature study method. Data were collected from relevant scientific sources, including journal articles and books, and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the teaching assistance program plays a significant role in shaping students’ professionalism through direct school experience. Furthermore, students’ ethical readiness and teaching performance improved, particularly in responsibility, discipline, teaching skills, and interaction with students. Therefore, the program contributes to preparing prospective teachers to become professional educators.